2016
DOI: 10.1038/srep32777
|View full text |Cite|
|
Sign up to set email alerts
|

Alterations of mitochondrial dynamics allow retrograde propagation of locally initiated axonal insults

Abstract: In chronic neurodegenerative syndromes, neurons progressively die through a generalized retraction pattern triggering retrograde axonal degeneration toward the cell bodies, which molecular mechanisms remain elusive. Recent observations suggest that direct activation of pro-apoptotic signaling in axons triggers local degenerative events associated with early alteration of axonal mitochondrial dynamics. This raises the question of the role of mitochondrial dynamics on both axonal vulnerability stress and their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 71 publications
2
17
0
Order By: Relevance
“…This observation is in line with the recent correlation between Mortalin up-regulation and inhibition of Fis1, a Drp1 mitochondrial receptor, upon antioxidant treatment of hepatocytes (Liu et al, 2017). Our data also further document the fundamental importance of mitochondrial dynamics in axons at the early stages of neurodegeneration (Annweiler et al, 2014;Kim et al, 2015;Lassus et al, 2016;Magnifico et al, 2013;Szelechowski et al, 2014). It should, however, be reminded that mitochondrial dynamics is also required for essential processes regulating cellular physiology, particularly in neurons, such as mitochondrial transport or quality control through mitophagy, as well as synaptic activity.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This observation is in line with the recent correlation between Mortalin up-regulation and inhibition of Fis1, a Drp1 mitochondrial receptor, upon antioxidant treatment of hepatocytes (Liu et al, 2017). Our data also further document the fundamental importance of mitochondrial dynamics in axons at the early stages of neurodegeneration (Annweiler et al, 2014;Kim et al, 2015;Lassus et al, 2016;Magnifico et al, 2013;Szelechowski et al, 2014). It should, however, be reminded that mitochondrial dynamics is also required for essential processes regulating cellular physiology, particularly in neurons, such as mitochondrial transport or quality control through mitophagy, as well as synaptic activity.…”
Section: Discussionsupporting
confidence: 90%
“…Mitochondrial dysfunction and oxidative stress occur early and distally in the pathological process of neurodegeneration. We previously showed that mitochondrial physiology strongly gates axonal vulnerability towards direct axonal insults and that high doses of rotenone are needed to trigger direct axonal degeneration (Lassus et al 2016). Thus, we addressed the influence of Mortalin expression on axonal integrity and sensitivity to oxidative stress, using rat primary cortical neurons grown in microfluidic devices and transduced with LV-Mort, LV-shMortalin or LV-shScr.…”
Section: Mortalin Expression Levels Drive Axonal Sensitivity To Mitocmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychiatric disorders (neurodegenerative diseases) occur after a series of intriguing incidences such as inflammatory dysfunctions and increased neuroinflammation (peripheral and central nervous system) 1 . These factors collectively activate microglia cells (immune and structural cells) to induce the release of pro-inflammatory cytokines interleukin (IL) -1β, (IL) -18, and tumor necrosis factor-alpha (TNF) -α, that initiates neuronal damages and trigger neuron death 2 . These cells further released fragmented and dysfunctional mitochondria into the brain tissue milieu.…”
Section: Introductionmentioning
confidence: 99%